Promotional effects of trace Ni on its dual-functional electrocatalysis of Co/N-doped carbon nanotube catalysts for ORR and OER. (8th February 2022) - Shi, Yuande; Cai, Jiannan; Zhang, Xiaofeng; Li, Zhongshui; Lin, Shen
Abstract: It is still a great challenge for developing efficient dual-functional electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The electrocatalysts are critical to enhance the efficiency of metal-air cells and fuel cells. In this study, a one-pot vapor deposition method was used to realize the synchronously dope of N and Ni (trace) into Co/C to form Co–Ni (trace)/N-doped carbon nanotubes (Co–Ni (trace)/NCNTs). An interesting result is that injecting dicyandiamide (DCD) into Ni foam as a precursor led to the in situ formation of NCNTs, with synchronous doping of trace Ni into Co species. The cooperative effects of the Co–Ni (trace) and N-doped carbon nanotubes resulted in superior dual-functional electrocatalytic performance of Co–Ni (trace)/NCNTs for the ORR (half-wave potential E1/2 vs. RHE: 0.83 V, electron transfer number n: 3.97) and OER (overpotential vs. RHE: 337 mV at 10 mA cm −2, Tafel slope: 94.0 mV dec −1 ). Moreover, the Co–Ni (trace)/NCNTs catalyst showed excellent stability during 20, 000 s of durability testing for both ORR and OER. This study provides a feasible strategy for designing efficient nonnoble metal-catalysts for renewable energy conversion devices. Graphical abstract: Image 1 Highlights: The Co–Ni (Trace)/NCNTs was prepared by in situ vapor deposition at high temperature. The Co–Ni (Trace)/NCNTs shows superior electrocatalysis and stability for both ORR and OER. The existence of NCNTs helps to improve conductivity of the composite. Highly dispersive trace Ni particles contribute to enhance catalytic activity of Co.